Effect of heat treatment on hardness, density and color of Populus × canadensis ‘I-214’ wood - Carla Taraborelli; Silvia Monteoliva; Gabriel Keil; Eleana Spavento (Forest Systems, 2022)
Aim of study: To evaluate the effect of heat treatment (HT) on hardness, density and color of Populus × canadensis ´I-214´ (poplar) wood.